AGRICULTURAL PRODUCTION, OCCUPATION AND A WAY OF LIFE - Purić, Sveto; Purić, Jelena; Gligić Savić, Anja (Economics of Agriculture, 2012)
If you want the best for agriculture, you cannot separate agriculture as a business and agriculture as a way of life. If you do separate them, the question is what will remain from either of the two. If you do not connect them, national food stability is jeopardized, but the question of safety is seriously entered. Good experiences of others are useful and good, ones own are more useful and better. The food cultivated on the living and working territory of a man suits him the best. The other one, besides the high prices, is the necessary evil. With that, it burdens the balance of payments, instead of surplus, it makes the deficit. Moreover, it does not feel good. Finally, where is the pleasure of occupation in agriculture and animal husbandry?! Disparity of the production time and working time, seasonal character of the agricultural production and slower capital turnover are a serious reason for this sector to be the subject of a special attention and help by the state, but not a sector with special presence of negligence and nondomestic treatment. Sooner or later you will have to deal with that problem.